2020
DOI: 10.1186/s12967-020-02533-3
|View full text |Cite
|
Sign up to set email alerts
|

A SWATH-MS analysis of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome peripheral blood mononuclear cell proteomes reveals mitochondrial dysfunction

Abstract: Background Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a serious and complex physical illness that affects all body systems with a multiplicity of symptoms, but key hallmarks of the disease are pervasive fatigue and ‘post-exertional malaise’, exacerbation after physical and/or mental activity of the intrinsic fatigue and other symptoms that can be highly debilitating and last from days to months. Although the disease can vary widely between individuals, common symptoms also i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 52 publications
6
63
5
2
Order By: Relevance
“…Within the regulatory regions of protein-coding genes investigated in the Helliwell study, it is worthwhile noting that the gene encoding the Complex 1 subunit NDUFA11 was hypomethylated [ 84 ]. This is consistent with the elevated Complex 1 expression evident in this and our previous study of lymphoblasts [ 2 ], as well as the same authors’ study of PBMCs [ 66 ]. Continued epigenetic studies utilising different cell types would be valuable, since it may be possible that in proliferative cell types such as lymphoblasts, factors such as altered gene expression programmes or glutamine depletion are accentuated and thus may impact DNA methylation status to a greater degree than in PBMCs.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Within the regulatory regions of protein-coding genes investigated in the Helliwell study, it is worthwhile noting that the gene encoding the Complex 1 subunit NDUFA11 was hypomethylated [ 84 ]. This is consistent with the elevated Complex 1 expression evident in this and our previous study of lymphoblasts [ 2 ], as well as the same authors’ study of PBMCs [ 66 ]. Continued epigenetic studies utilising different cell types would be valuable, since it may be possible that in proliferative cell types such as lymphoblasts, factors such as altered gene expression programmes or glutamine depletion are accentuated and thus may impact DNA methylation status to a greater degree than in PBMCs.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, elevated fatty acid β-oxidation suggested by Germain et al is also consistent with our observations here, if the rates of fatty acid β-oxidation are indeed upregulated in accordance with expression of the enzymes involved [10]. Sweetman et al observed elevated levels of enzymes involved in ketone body metabolism in the proteomes of ME/CFS PBMCs, which could indicate increased oxidation of fatty acids and their derivatives through the TCA cycle [66]. More strikingly within this same study, acyl-CoA dehydrogenases and the beta subunit of mitochondrial trifunctional enzyme (HADHB), specifically, were elevated in their expression in PBMCs [66]-an observation shared in our own work here with lymphoblasts.…”
Section: Preferential Fatty Acid β-Oxidation and Dysregulated Intracesupporting
confidence: 93%
See 3 more Smart Citations